Viewing Romantic and Friendship Interactions Activate Prefrontal Regions in Persons With High Openness Personality Trait - Azhari, Atiqah; Rigo, Paola; Tan, Pei Yu; Neoh, Michelle Jin-Yee; Esposito, Gianluca (Frontiers in Psychology, 2020)
The personality traits we have and the closeness we experience in our relationships inevitably colour the lenses through which we perceive social interactions. As such, the varying perceptions and experience of our social relationships could be representative of underlying differences in neural processes occurring in the prefrontal cortex (PFC) involved in processing affective information and social cognition. However, little is known of how personality traits and relationship closeness with others influence brain responses when viewing social interactions between kin (i.e. siblings) and non-kin (i.e. romantic, friends) partners. In the present study, functional near-infrared spectroscopy (fNIRS) was employed to investigate prefrontal cortical activation patterns in response to three 1-minute mute videoclips depicting a male–female couple interacting with comparably mild levels of affection while baking, exercising, and eating. The context of the interaction was modulated by informing participants about the type of relationship each couple in the three video clips were in: (a) romantic partners, (b) friends, or (c) siblings. By changing only the contextual labels of the videos, we revealed distinct PFC responses to relationship type as a function of openness trait, closeness with romantic partner and closeness with siblings. As openness score increased, we observed an enhanced activation of the left inferior frontal gyrus (IFG), the left anterior PFC (aPFC) and the right frontal eye fields (FEF) in response to the video labelled romantic and friendship, but a reduction in these areas in the siblings condition. Similarly, individuals with higher romantic and sibling closeness showed increased activation in the IFG and dorsolateral PFC in response to romantic and friendship conditions, but decreased activation in the siblings condition. Differences in PFC activations towards romantic, platonic, and sibling relationships reflect underlying variations in the cognitive processing of social interactions, depending on the personality (i.e. openness) and experiences (i.e. relationship closeness) of the individual, and the relationship type by which the interaction is labeled as.